(untitled) (Stato, Chiese e pluralismo confessionale, 2011)
Il contributo è pubblicato con il permesso della Brigham Young University Law Review - dove è apparso nel vol. n. 2 del 2010 (Tribute to Professor Michael Goldsmith), alle pp. 101-148) - e dell‖Autrice, che ringraziamo sentitamente. SUMMARY: 1. Introduction - 2. History of and Motivations for the OIC Defamation of Religions Resolutions - 2.a - The OIC Exerts a Concerted Effort to Protect Islam - 2.b - Terrorist Attacks and Danish Cartoons Raise the Stakes - 3. Defamation of Religions: A Permissible Restraint on Freedom of Speech and Expression? - 3.a - History, Basic Elements, and Contemporary Usage of Defamation - 3.b - Interaction Between Defamation of Religions and the Basic Human Rights Enumerated in Major International Instruments - 4. The Evolution of a Resolution - 4.a. 1999-2000: Beginnings - 4.b. 2001: A Pre-9/11 World - 4.c. 2002: Reactions to the Violent Backlash Against Muslims - 4.d. 2003-2004: Fluctuations in Support - 4.e. 2005: Intensification of a Campaign - 4.f. 2006-2007: The Move to the General Assembly - 4.g. 2008: Decreasing Margins of Support - 4.h. 2009: Current Resolution and Recommendations for Application - 5. Consequences of Accepting the Resolutions and Subsequent Enactment of Statutes Designed to Prevent Defamation of Religions - 5.a. Human Rights Committee - 5.b. The European Court of Human Rights - 5.c. Blasphemy, Incitement, and Hate Speech Laws and Their Enforcement - 5.d. Possible Future Statutes and Enforcement Under Defamation of Religions Theory - 6. Alternatives to Defamation of Religions in the U.N. Resolutions - 7. Conclusion.